2004
DOI: 10.1002/lsm.20038
|View full text |Cite
|
Sign up to set email alerts
|

Long pulse Nd:YAG laser for treatment of leg veins in 40 patients with assessments at 6 and 12 months

Abstract: The long-pulsed Nd:YAG laser offered efficient treatment of leg veins. Side effects were minimal and transient. The edge-detection program may help patients appreciate better the actual results of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…Previous reports indicate excellent results for telangectasias with accompanying improved skin safety 13, 14. Patients should be given realistic expectations as computer analyses typically yields more improvement than is seen by the human eye during assessments 15.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports indicate excellent results for telangectasias with accompanying improved skin safety 13, 14. Patients should be given realistic expectations as computer analyses typically yields more improvement than is seen by the human eye during assessments 15.…”
Section: Discussionmentioning
confidence: 94%
“…Further developments of long-pulsed Nd:YAG technology have allowed the delivery of a macropulse that could vary depending on the size and depth of leg veins [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study involving 50 women undergoing up to three treatment sessions at 6-week intervals reported that more than 80% achieved greater than 75% obliteration of their telangiectasias and reticular veins, with 76% patient satisfaction [38]. A third study with 40 female patients undergoing up to three treatment sessions 6 weeks apart reported patient satisfaction rates of 42.5% at 6 months and 75% at 12 months and objective improvement rates, based on photographic results, of 57% at 6 months and 82.5% at 12 months [39]. Procedure Patients undergo skin cooling with water-cooled chambers applied to the skin, cooling coupling gel, air-blowing cooling devices, or refrigerated cooling sprays before and after the procedure to provide comfort during the procedure and to minimize postprocedure side effects [40].…”
Section: Effi Cacymentioning
confidence: 98%